PENGARUH BRAND IMAGE DAN ENDORSEMENT SELEBRITAS TIKTOK TERHADAP MINAT BELI - Fadhilah Shabirah; Taufik Bustami; Dedy Wahyudi (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to determine the influence of brand image and TikTok celebrity endorsements on purchase intention for Scarlett skincare products among Generation Z in Bengkulu City. This research is a quantitative descriptive study. The population of this study was Generation Z in Bengkulu City. Data collection techniques used were observation and questionnaires. The data analysis technique used was multiple linear regression. The results of this study indicate that brand image and TikTok celebrity endorsements have a positive and significant influence on purchase intention. This finding suggests that the higher the positive consumer perception of the brand image, and the more effective and credible the endorsement by TikTok celebrities, the higher the consumer's purchase intention for Scarlett skincare products. This research provides important implications for companies in designing more targeted and effective marketing strategies, particularly in utilizing social media as a primary promotional tool. Keywords: Brand Image, TikTok Celebrity Endorsement, Purchase Intention